The incidence and clinical characteristics of placental insufficiency among high-risk pregnancies with normal umbilical artery resistance index after 32 weeks gestation : a cross-sectional study - Van der Merwe, Elrike (Stellenbosch : Stellenbosch University, 2015)
Thesis (MMed)--Stellenbosch University, 2016.